Emotional labour demands and work engagement in Portuguese police officers. (4th March 2023) - Oliveira, Soraia; Pinto, Ana; Carvalho, Carla; de Moura, Rui Coelho; Santos-Costa, Paulo; Gondim, Sonia
ABSTRACT: Grounded in the Emotional Labour Theory, we aim to study the relationship between emotional demands (the expression of positive emotions and suppression of negative emotions) and work engagement in a sample of Portuguese police officers. We intend to explore the possible effects of these emotional demands on work engagement and ways of preventing and/or mitigating its impact. When analysing the studies conducted in the Portuguese police context, we found a gap regarding emotions and/or emotional regulation. Accordingly, a sample of 924 Portuguese police officers from the Public Security Police (PSP) answered the Emotion Work Requirements Scale and the Utrecht Work Engagement Scale voluntarily. Through correlation and multiple linear regression, we found a relationship between these emotional demands toward different interpersonal interactions and work engagement. We discuss these results, providing suggestions for field intervention and clues for future research.